Independent component analysis of streamwise velocity fluctuations in turbulent channel flows - Wu, Ting; He, Guowei (Theoretical and applied mechanics letters, 2022)
•ICA is employed to decompose streamwise velocity fluctuations in turbulent channel flows into multiscale localised modes.•The height and size are introduced to quantify the spatial characteristics of ICA modes.•ICA modes are typically localised in space.•The sizes of ICA modes are multiscale and are approximately proportional to their heights. Independent component analysis (ICA) is used to study the multiscale localised modes of streamwise velocity fluctuations in turbulent channel flows. ICA aims to decompose signals into independent modes, which may induce spatially localised objects. The height and size are defined to quantify the spatial position and extension of these ICA modes, respectively. In contrast to spatially extended proper orthogonal decomposition (POD) modes, ICA modes are typically localised in space, and the energy of some modes is distributed across the near-wall region. The sizes of ICA modes are multiscale and are approximately proportional to their heights. ICA modes can also help to reconstruct the statistics of turbulence, particularly the third-order moment of velocity fluctuations, which is related to the strongest Reynolds shear-stress-producing events. The results reported in this paper indicate that the ICA method may connect statistical descriptions and structural descriptions of turbulence.